1995
DOI: 10.1093/oxfordjournals.jbchem.a124898
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Expression of Xenopus Midkine Gene during Early Development1

Abstract: Midkine (MK) is a heparin-binding growth factor and forms a novel protein family together with another member, pleiotrophin (PTN)/heparin-binding growth-associated molecule (HB-GAM). A cDNA clone isolated from Xenopus laevis specifies for the Xenopus counterpart of MK (XMK), and the mode of XMK expression was studied by in situ hybridization and Northern blot analysis. XMK was first expressed at stage 11 (middle gastrula) and was located in the neural anlage at stage 12 (late gastrula). Through stage 13 to 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…As Factor XIIIa is larger than tissue transglutaminase (ϳ300 kDa versus 80 kDa), the cross-linking of MK molecules may not be performed by Factor XIIIa, even though it can stimulate putrescine incorporation into MK molecules. It is notable that these three acyl-donating Gln residues are conserved among the MK/ PTN family, whereas the other two Gln residues are not (48). As can be seen in Fig.…”
Section: Discussionmentioning
confidence: 88%
“…As Factor XIIIa is larger than tissue transglutaminase (ϳ300 kDa versus 80 kDa), the cross-linking of MK molecules may not be performed by Factor XIIIa, even though it can stimulate putrescine incorporation into MK molecules. It is notable that these three acyl-donating Gln residues are conserved among the MK/ PTN family, whereas the other two Gln residues are not (48). As can be seen in Fig.…”
Section: Discussionmentioning
confidence: 88%
“…10 and 11). MK modulates epithelial-mesenchymal interactions during fetal development and organogenesis in the mouse (12) as well as in Xenopus (13). From in vitro cell biology studies and the embryonic expression pattern of MK in the central nervous system it was concluded that MK directs neurite interconnections during an early phase of brain development and may later on have a maintenance function in some restricted areas.…”
mentioning
confidence: 99%
“…Furthermore, elimination of HS-PG by heparitinases induced abnormal mesodermal differentiation. Embryogenesis is thought to be regulated by signaling factors, such as FGFs (7), bone morphogenetic proteins (8,9), activin (10,11), midkine (12), hepatocyte growth factor (13), Vg1 (14), Wnt (15,16) and Sonic Hedgehog (17), which are expressed in early stages in Xenopus embryogenesis. Since most of these growth factors have a heparin (HP)/HS binding property, at least some of these signaling factors, probably exert their functions during embryogenesis through interactions with HS-PG.…”
mentioning
confidence: 99%